2023
DOI: 10.1111/cod.14408
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis and sequelae of meth(acrylate) sensitization in beauticians and consumers of manicure materials

María E. Gatica‐Ortega,
Laura Rodríguez‐Lago,
Pedro Beneyto
et al.

Abstract: BackgroundAllergic contact dermatitis from (meth)acrylic monomers (ACDMA) in manicure products is increasing.ObjectiveTo evaluate the prognosis, work performance impairment and sequelae of a cohort of beauticians and manicure consumers with ACDMA sensitized from the exposure to manicure products.MethodsWe conducted a telephone survey with patients diagnosed with ACDMA.ResultsOne hundred and six patients were evaluated, including 75 (70.8%) beauticians and 31 (29.2%) consumers. All were women with a mean age of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 40 publications
0
7
1
Order By: Relevance
“…The overall frequency of sensitization to 2-HEMA in the 4-year study period was identified to be 4.3%, which is higher than the frequency found by prior research conducted by GEIDAC 10 18 The percentage of positive reactions to HEMA was likely underestimated since D7 readings were only performed in a low proportion of cases.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…The overall frequency of sensitization to 2-HEMA in the 4-year study period was identified to be 4.3%, which is higher than the frequency found by prior research conducted by GEIDAC 10 18 The percentage of positive reactions to HEMA was likely underestimated since D7 readings were only performed in a low proportion of cases.…”
Section: Discussioncontrasting
confidence: 56%
“…26,27 Incontinence pads have been described as possible causes of eczema in (meth)acrylate-sensitized patients. [28][29][30][31] One patient developed scaly eczematous fingertip reactions following contact with glues and different materials while making miniature models. One patient sensitized to 2-HEMA recalled eczematous reactions from the exposure to a specific brand of running shoes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five of our patients, who were primarily sensitized to nail cosmetics, later had allergic reactions to other (meth)acrylate‐containing products such as dental products (of who one developed occupational ACD when she started working as a dental assistant) and TENS‐electrodes. Such secondary reactions have previously been observed to dental materials such as dental fillings and restoration, orthodontic or occlusal splint materials and desensitizing dental swabs, 13–19 knee prostheses (bone cement) 20 and incontinence pads 21 . In a recent study, secondary reactions to printing inks, paints, 16 glues and sanitary napkins were also mentioned 13 .…”
Section: Discussionmentioning
confidence: 80%
“…Such secondary reactions have previously been observed to dental materials such as dental fillings and restoration, orthodontic or occlusal splint materials and desensitizing dental swabs, 13–19 knee prostheses (bone cement) 20 and incontinence pads 21 . In a recent study, secondary reactions to printing inks, paints, 16 glues and sanitary napkins were also mentioned 13 . Fifteen per cent of patients sensitized by nail cosmetics later reacted to dental materials and 25% to sanitary napkins.…”
Section: Discussionmentioning
confidence: 84%